2020
DOI: 10.5336/jtracom.2020-73402
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Death Anxiety and Affecting Factors of Nurses and Doctors' Working in a State Hospital: Artvin Example

Abstract: Ölüm kavramı günümüzde gizemini ve güncelliğini koruyan, üzerine birçok çalışmalar yapılan ve yaşayan tüm organizmaların deneyimleyeceği kişiye özel ve evrensel bir olaydır. Tanımı kolay olmayan ölüm olgusuna verilen anlam, kültürden kültüre ve kişiden kişiye değişmiştir. 1,2 Bununla birlikte hemşi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the present study, the TPDAS score of nurses in the 36–41 age group was found to be significantly lower than the other age groups. There are studies in the literature indicating that there is no relationship between death anxiety and age 13,14 . There are also studies that older nurses have a more positive approach to death 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the TPDAS score of nurses in the 36–41 age group was found to be significantly lower than the other age groups. There are studies in the literature indicating that there is no relationship between death anxiety and age 13,14 . There are also studies that older nurses have a more positive approach to death 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study conducted by Kösedağ (2021) [12], it was found to be 29.44±9.13. Likewise, in other studies conducted in Türkiye, nurses were found to have a moderate level of fear of death [25,26]. In studies conducted after the pandemic, it was determined that level of death fear of nurses was moderate or high [10,27].…”
Section: What Are the Levels Of Cf Ts And Pc Of Nurses?mentioning
confidence: 92%
“…In this study, it was concluded that the mean TS score of the nurses was 30.69±12. 26 and it was at a moderate level. Similarly, in a study conducted by Kösedağ (2021) [12], it was found to be 29.44±9.13.…”
Section: What Are the Levels Of Cf Ts And Pc Of Nurses?mentioning
confidence: 97%
“…In studies focusing on nursing and anxiety, issues of self-esteem (Özen-Kutanis & Tunç, 2013) and death anxiety in nurses working in hospital settings have been examined (Yorulmaz & Kurt-Sezer, 2020).…”
Section: Introductionmentioning
confidence: 99%